Effect of Graft Geometric Parameters on Shear Stress Applied to the Coronary Artery in Bypass Surgery - Moradian, Khadije; Dehghan, Fatemeh (Mechanical Technology and Engineering Insights, 2025)
Cardiovascular Diseases (CVDs) are among the most common causes of death worldwide. One of the treatment methods is grafting a vessel from the upstream area to the aortocoronary artery and from the downstream area to the region beyond the coronary artery blockage, performed during bypass surgery. In the present study, the effect of geometric parameters (graft angles and distances) on velocity and Wall Shear Stress (WSS) applied to the coronary artery is investigated. The maximum velocity occurs at the center of the stenosis in the main vessel, decreasing toward the wall. An increase in velocity gradient leads to increased shear stress, which may damage the vessel wall. The maximum velocity and minimum shear stress occur at a 5-degree angle. The optimal condition for surgery at 95% stenosis is a graft angle of 15 degrees and a distance of 10 mm from the stenosis location, because the shear stress value is minimized.